A Trade fair certification from the perspective of sustainable development: the case of the Casa Apis - Maria Mislene Rosado de Sousa (2014)
The present study examined Fairtrade certification from the perspective of sustainable development, with a focus on social, cultural, environmental, economic and political factors taking into account the perception of the actors in charge of the first part of the global value chain of the Central of Apicultural Cooperatives in Brazilian Semiarid - CASA APIS. Casa Apis is a solidary enterprise structured under PROMEL, a program to generate employment and income and combat poverty in the Northeast of Brazil. The Central aforementioned is located in the city of Picos-PI and currently gives assistance to about 960 beekeepers that are placed in 08 cooperatives in 52 municipalities in PiauÃ and CearÃ. With a view to improving the competitiveness of cooperatives, Casa Apis seeks constantly to obtain the seals of the most important beekeeping industry certifications, including certification of Fair Trade, which was acquired in 2007 and made it the first certified apicultural exporter cooperative in Brazil. Fair-trade certification primarily aims at the sustainable development of small producers organizations by checking the fulfilling of policies and principles which value the small producer, who formerly had an unfair treatment in the traditional trade model, especially in relation to payment. These principles are supported by the Sustainable Development proposal. According to Sachs (2009), equity in social, cultural, environmental, economic, and political aspects, among others, is essential for Sustainable Development. We chose Casa Apis as an object of this study because of its importance for the sustainable development of the Brazilian semiarid region. Fairtrade certification requires sustainable development through production practices and trade which are socially fair, environmentally-oriented and economically ethical. This case study adopted content analysis and triangulation methods to analyze data (BARDIN, 2011; YIN (2011). We found out that Fairtrade certification promotes Sustainable Development from the perspective of the dimensions chosen for the study. Nevertheless, it was observed that the model of development within these dimensions are not equally developed as proposed in the model of Sachs (2009), but is still in process of development